Urine Catheter Sterilization from Adhered Biofilm Using Bimetallic Nanoparticles Synthesized Using the Plasma Reduction Method - Mohammed F. Al–Marjani; Fatima J. Hassan; Raghad S. Mohammed; Nisreen Kh. Abdalameer; Javed Iqbal (Al-Mustansiriyah Journal of Science, 2025)
Background: Bacterial infections, particularly those in medical devices such as urinary catheters, are a significant clinical challenge due to structural differences between Gram-positive and Gram-negative bacteria influencing their susceptibility to antimicrobial agents. As antibiotic resistance increases, core/shell nanoparticles are being explored as potential alternatives. Objective: This study investigates the antibiofilm properties of MgO/ZnO and CuO/ZnO nanoparticles at concentrations of 10 and 40 µg/mL, respectively, against common bacterial pathogens, specifically Klebsiella pneumoniae, Escherichia coli, and Staphylococcus aureus, and their potential to sterilize urinary catheters. Methods: A 96-well microtiter plate was used to determine sublethal dosage levels (Sub-MIC) and minimum inhibitory concentrations (MIC) to evaluate antibacterial activity. Antibiofilm performance was evaluated by measuring biofilm reduction, while antiadhesion assays were conducted on urinary catheters to determine the ability of nanoparticles to prevent E. coli attachment. Results: The nanoparticles exhibited strain-dependent antibacterial effects. S. aureus and showed high sensitivity to CuO/ZnO NPs, while E. coli and K. pneumoniae were less susceptible. Notably, Gram-negative pneumococci demonstrated resistance to MgO/ZnO and CuO/ZnO nanoparticles. In terms of biofilm inhibition, MgO/ZnO NPs were slightly more effective against S. aureus and E. coli, whereas CuO/ZnO NPs showed superior activity against K. pneumoniae. Biofilm formation was reduced by up to 56.32% at sub-MIC concentrations. In catheter adhesion assays, MgO/ZnO NPs inhibited E. coli adhesion by 64.59%, compared to 60.92% for CuO/ZnO NPs. This development refers to the effective adhesion of CuO/ZnO NPs to the catheter surface. The study also presented an efficient, feasible and simple procedure of coatings of MgO/ZnO and CuO/ZnO NPs to prevent biofilm adhesion to catheter surfaces. Conclusions: MgO/ZnO and CuO/ZnO nanoparticles demonstrated potent anti-biofilm activity, inhibiting bacterial growth, biofilm formation, and catheter adhesion. However, more research is needed on cytotoxicity, biocompatibility, and long-term effects.